2009
DOI: 10.1083/jcb.200812132
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of skeletal muscle α-actin–null mice by cardiac (fetal) α-actin

Abstract: Skeletal muscle α-actin (ACTA1) is the major actin in postnatal skeletal muscle. Mutations of ACTA1 cause mostly fatal congenital myopathies. Cardiac α-actin (ACTC) is the major striated actin in adult heart and fetal skeletal muscle. It is unknown why ACTC and ACTA1 expression switch during development. We investigated whether ACTC can replace ACTA1 in postnatal skeletal muscle. Two ACTC transgenic mouse lines were crossed with Acta1 knockout mice (which all die by 9 d after birth). Offspring resulting from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Up to 20% of cardiac muscle actin consists of the skeletal muscle ␣-actin isoform (34). The cardiac and skeletal muscle ␣-actin isoforms are 99% identical, with only four amino acid differences (27), and they have similar functions in postnatal skeletal muscle (35). The multiple ZASP isoforms may play unique roles in maintaining the Z-disc structure by interacting with ␣-actin in heart as well as skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Up to 20% of cardiac muscle actin consists of the skeletal muscle ␣-actin isoform (34). The cardiac and skeletal muscle ␣-actin isoforms are 99% identical, with only four amino acid differences (27), and they have similar functions in postnatal skeletal muscle (35). The multiple ZASP isoforms may play unique roles in maintaining the Z-disc structure by interacting with ␣-actin in heart as well as skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, switching of actin isoforms from -cardiac to -skeletal actin during development has been approved at the molecular level. Nowak et al currently reported that a line of -skeletal actin knockout mice survived to old age instead of dying soon after birth, when they were crossed with high expressing -cardiac actin transgenic mice (Nowak et al 2009). Although their Wndings indicate that -cardiac actin can eVectively replace the skeletal isoform in postnatal skeletal muscle tissues, they neither show precise functional diVerences between these two isoforms nor explain their alternating expression during development.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in other systems have demonstrated that actin isoforms have the capacity to up-regulate their transcription in an attempt to compensate for a functional perturbation or deregulation of the system (Kumar et al, 1997; Nowak et al, 2009; Diss et al, 2014). While some of these studies have found that this overexpression is not compensatory and does nothing to rescue the function of the muscle (Fyrberg et al, 1998; Crawford et al, 2002), here we show a system in which low levels of ectopic expression of a distinct actin isoform can rescue sarcomere structure to provide functional compensation.…”
Section: Discussionmentioning
confidence: 99%
“…In alpha-cardiac-actin deficient mice, vascular smooth muscle and skeletal actins increased expression in the heart (Kumar et al, 1997). Likewise, alpha-cardiac-actin and vascular specific actins were increased in alpha-skeletal-actin deficient mice and human nemaline myopathy patients (Crawford et al, 2002; Nowak et al, 2007, 2009). However, this compensatory up-regulation of alternative actin isoforms does not restore muscle function and does not bring total actin levels back to normal (Kumar et al, 1997; Perrin and Ervasti, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation